Hubbard Model Calculations for Zinc Oxide Semiconductor - Ali, Aqeel (University of Thi-Qar Journal of Science, 2023)
To investigate the effects of Hubbard on-site Coulombic correction on the structural and electronical characteristics of wurtzite zinc oxide, first-principles calculations using density functional theory (DFT) were carried out. Because of the changes in structural characteristics brought about by the correction of hybridization between Zn 3d and O 2p states, suitable Hubbard terms need to be constructed before one can make an accurate forecast of the properties of ZnO. The computations were carried out by applying Hubbard corrections Ud to Zn 3d states and Up to O 2p states. These adjustments were based on the Wu-Cohen functional. When the Hubbard corrections Ud and Up were introduced to the calculation, the lattice parameters were more comparable to the experimental data and were found to be accurately predicted. The combination of the correction terms Ud and Up was successful in improving the underestimated bandgap of the wurtzite ZnO, which may have solved the difficulties that are associated with the traditional DFT. There is a strong agreement between the experimental bandgap and the best Hubbard parameters that were discovered for GGA-WC+U. These parameters were found to be Ud = 8 eV and Up = 8 eV.